Influence Of Personal Factors To The Problem Of Social Orphanhood - Musabayeva, A.; Uasheva, A.; Rakisheva, A. (3RD CYPRUS INTERNATIONAL CONFERENCE ON EDUCATIONAL RESEARCH (CY-ICER 2014), 2014)
This article investigates the causes of social orphanhood due to the increasing number of abandoned and neglected children. The article focuses on studying the influence of personal factors on social orphanhood, namely the problem of mother abandoning the child. The issue must be discussed diligently and action must be taken in order to stop the increase of the consequences that arise as a result and feature of phenomenal social abandonment of newborns by their mother. Become victims of circumstances such as poverty, lack of education, unemployment thereby giving rise to deviant and delinquent behavior which in turn becomes the basic unbalanced behavior of an individual. This has a very negative effect on social institutions and the society in general. In this article we studied the personal factors of child abandonment and tried to show them in two ways: based on maternal deprivation of mother and on their socialization in childhood. Problems that women abandoned a child are not only the result of the lack of property, money, work. But mostly it is based on a legacy of personal and family matters related to disadvantage of previous generations and forgetfulness of immediate needs of people and especially children.
Keywords: social orphanhood, implementation of international norms, personal factors of child abandonment, socialization in childhood